Deciphering the binding between Nupr1 and MSL1 and their DNA-repairing activity. - David Aguado-Llera (Public Library of Science (PLoS), 2013)
The stress protein Nupr1 is a highly basic, multifunctional, intrinsically disordered protein (IDP). MSL1 is a histone acetyl transferase-associated protein, known to intervene in the dosage compensation complex (DCC). In this work, we show that both Nupr1 and MSL1 proteins were recruited and formed a complex into the nucleus in response to DNA-damage, which was essential for cell survival in reply to cisplatin damage. We studied the interaction of Nupr1 and MSL1, and their binding affinities to DNA by spectroscopic and biophysical methods. The MSL1 bound to Nupr1, with a moderate affinity (2.8 µM) in an entropically-driven process. MSL1 did not bind to non-damaged DNA, but it bound to chemically-damaged-DNA with a moderate affinity (1.2 µM) also in an entropically-driven process. The Nupr1 protein bound to chemically-damaged-DNA with a slightly larger affinity (0.4 µM), but in an enthalpically-driven process. Nupr1 showed different interacting regions in the formed complexes with Nupr1 or DNA; however, they were always disordered ("fuzzy"), as shown by NMR. These results underline a stochastic description of the functionality of the Nupr1 and its other interacting partners.